The Impact of the Insurance and Actuarial Olympics on High School and Vocational High School Students’ Interest in Pursuing a College Degree in Insurance - Antony Japari; Antonius Anton Lie; Fanny Novika; Enno Karina Fandayani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
Students' interest in pursuing higher education in insurance and actuarial science in Indonesia remains relatively low despite the increasing demand for qualified professionals in these fields. This study aims to examine the effect of the Insurance and Actuarial Olympiad on students' study interest and to investigate the mediating roles of Learning Motivation and Career Perception. A quantitative survey approach was employed involving 151 participants of the Insurance and Actuarial Olympiad from various secondary schools in Indonesia. Data were collected through a questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that Olympiad Implementation has a positive and significant effect on Learning Motivation (β=0.645; p<0.001) and Career Perception (β=0.502; p<0.001). Furthermore, Learning Motivation (β=0.366; p=0.006) and Career Perception (β=0.438; p<0.001) positively and significantly influence Study Interest. However, the direct effect of Olympiad Implementation on Study Interest is not significant (β=-0.090; p=0.340). The indirect effect analysis reveals that Learning Motivation and Career Perception significantly mediate the relationship between Olympiad Implementation and Study Interest. The model explains 43.7% of the variance in Study Interest. These findings suggest that the Insurance and Actuarial Olympiad effectively enhance students' interest in pursuing studies in insurance through increased learning motivation and more positive career perceptions.